Turkey : Fiscal Transparency Evaluation. - International Monetary Fund. Fiscal Affairs Dept. (Washington, D.C. : International Monetary Fund, 2017)
This paper discusses findings of the evaluation of fiscal transparency in Turkey. As a result of several reforms, Turkey has made significant progress against the 36 principles of the IMF's new Fiscal Transparency Code. Of the 36 principles in the Code, Turkey now meets 10 principles at the basic level, 13 principles at the good level, and 6 principles at the advanced level. Fiscal transparency practices are strongest in the area of fiscal reporting. Moreover, in 5 of the areas where Turkey's transparency practices do not currently meet basic practice, this could be readily addressed by publishing data that are already collected for internal management purposes.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet